EXPERIMENTAL SETTING FOR TESTING THE BOND STRENGTH BETWEEN METAL ALLOY AND PEEK - Zhivko Georgiev; Svetlin Alexandrov; Zlatina Tomova (Peytchinski Publishing, 2021)
Purpose: The aim of the article is to present an experimental setting for bending strength testing of metal specimens covered with PEEK. Materials and methods: Three groups of metal specimens made of cobalt chromium alloy are produced using the lost wax technique: group 1 - specimens with a smooth metal surface; group 2 - sand blasted metal surface; group 3 - sand blasted metal surface with retention crystals. The shape and size of the specimens are designed to correspond to the retentive elements of the apparatus for micro tension and micro pressure LMT 100. PEEK is pressed over the specimens, and after thermal cycling, the bond between metal alloy and PEEK is studied using bending strength three-point micro testing. Results and discussion: The experimental setting is focused on the type of specific contact surface between the two materials. The design corresponds to the requirements of apparatus LMT 100 and allows the production of a big number of specimens. Because of the thermal regime of BioHPP pressing, it is impossible to add groups of specimens using contemporary adhesives on the metal surface. Conclusion: Created specimens allow strength investigation by three-point bending micro testing. The experimental setting provides the production of a big number of specimens with the same shape and size.